2019
DOI: 10.1021/acs.cgd.9b00200
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Indomethacin Crystals into a Polymer Melt: Role of Diffusion and Fragmentation

Abstract: The dissolution or melting of a crystalline drug into a molten polymeric matrix underpins the fabrication of a number of drug delivery systems. However, little is known about how crystals dissolve in such viscous matrices. Herein, the heat-induced dissolution of indomethacin crystals into a molten polymer, copovidone, was evaluated, probing changes in crystal features at multiple length scales using various microscopy techniques. Diffusion of the drug into the polymer film was observed by elemental composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 98 publications
0
26
0
Order By: Relevance
“…Here, only a small temperature gradient exists from the core of the material to the surface, due to a cooling effect of the surrounding air [10]. It has been suggested that the in situ amorphization process is driven by dissolution/fusion of the drug into the polymer at temperatures above the glass transition temperature (T g ) of the polymer [9,11,12]. Since internal heating within the compact during microwaving induces the in situ amorphization process, it is fundamentally interesting whether heating using a convection oven would yield similar results.…”
Section: Introductionmentioning
confidence: 99%
“…Here, only a small temperature gradient exists from the core of the material to the surface, due to a cooling effect of the surrounding air [10]. It has been suggested that the in situ amorphization process is driven by dissolution/fusion of the drug into the polymer at temperatures above the glass transition temperature (T g ) of the polymer [9,11,12]. Since internal heating within the compact during microwaving induces the in situ amorphization process, it is fundamentally interesting whether heating using a convection oven would yield similar results.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested previously, that the amorphization process of a drug in a polymer, at temperatures above the T g of the polymer, follows a dissolution process and is enhanced with increasing temperature above this temperature threshold. 22,56 Additionally, it was suggested that the temperature of the compact increases faster above, than below the T m of PEG due to the increased mobility of liquid PEG, as compared to solid PEG. In the present study, the temperature was measured on the surface of the compacts during exposure to microwave radiation in order to correlate it to the obtained rate and degree of amorphization.…”
Section: Analysis Of the Temperature Of The Compacts During In Situ Drug Amorphization And The Amorphization Kineticsmentioning
confidence: 99%
“…On the other hand, physical mixture (Figure 9, band C) and solid co-evaporate (Figure 9, band D) of ETD with PEG 4000, showed complete disappearance of endothermic peak of the drug and the appearance of new endothermic peaks at both 58.9°C and 61.3°C for solid co-evaporate and physical mixture, respectively. The disappearance of ETD peak in case of physical mixture could be explained on the basis that the drug was dissolved in the molten polymer [46]. However, the complete disappearance of the endothermic peak of the ETD in its solid co-evaporate with PEG 4000 may be, also, attributed to the formation of the amorphous form of the drug [47].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%